PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA BAGI HASIL (DBH), DANA ALOKASI UMUM ( DAU ) DAN DANA ALOKASI KHUSUS ( DAK) TERHADAP ALOKASI BELANJA MODAL PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Fery Sumardi, 11.42.02.0108 (Jurnal Mahasiswa Pasca Sarjana, 2015)
Based on model testing procedure this research used Fixed Effect Model      ( FEM ). The results showed that Local Original Revenue (LOR), Revenue Sharing (RS), the General Allocation Fund (GAF) had a positive significant effect on Capital Expenditure Allocation ( CEA ) of 35 district / town government in Central Java Province while Special Allocation Fund (SAF) had no significant effect on  Capital Expenditure Allocation ( CEA .Keywords: Local Original Revenue, Revenue Sharing, General Allocation Fund, the Special Allocation Fund and Capital Expenditures.